DESAIN ANTENA MICROSTRIP RECTANGULAR ARRAY 1x4 PADA FREKWENSI 2.2 UNTUK RADAR KAPAL - Agus Dwi Santoso; Fery Budi Cahyono; Bambang Bagus Harianto (Jurnal Penelitian)
This study aims to analyze antennas' characteristics at a frequency of 2.2 GHz, including the value of return loss, VSWR, gain, bandwidth, surface current, and radiation pattern. The antenna characteristics have been designed using simulations made with FR-4 substrates with a dielectric constant ε_r= 4.3 and substrate thickness (h) = 1.6 mm and copper patches with a patch thickness of 0.035 mm. Single antennas are made first to get the desired parameters, then continue to make 1x2 and 1x4 antenna arrays. The feeding antenna array is arranged using the Wilkinson power divider technique on the side of the patch. Antenna array planning aims to increase the antenna gain value as well as the antenna directivity value. From the simulation results, successive values were obtained starting from a single antenna, a 1x2 antenna array, and a 1x4 antenna array which included return loss of -22 dB, 25.9 dB, and -15.3 dB. Swr values are 1.1,1.1,1,1.4 each. The gain values are 3.38 dB, 5.52 dB, 7.84 dB, respectively. Antenna bandwidth is obtained by 100 MHz, 400 MHz, and 200MHz. The angular width obtained is 99.40, 92.20, and 80.20.